Tandem autologous/reduced-intensity conditioning allogeneic stem-cell transplantation versus autologous transplantation in myeloma: long-term follow-up - Björkstrand, Bo; Iacobelli, Simona; Hegenbart, Ute; Gruber, Astrid; Greinix, Hildegard; Volin, Liisa; Narni, Franco; Musto, Pellegrino; Beksac, Meral; Bosi, Alberto; Milone, Giuseppe; Corradini, Paolo; et al. (Journal of clinical oncology, 2011)
Purpose - - Results of allogeneic stem-cell transplantation (allo) in myeloma are controversial. In this trial autologous stem-cell transplantation (auto) followed by reduced-intensity conditioning matched sibling donor allo (auto-allo) was compared with auto only in previously untreated multiple myeloma. - - Patients and Methods - - In all, 357 patients with myeloma up to age 69 years were enrolled from 2001 to 2005. Patients with an HLA-identical sibling donor were allocated to the auto-allo arm (n = 108) and patients without a matched sibling donor were allocated to the auto arm (n = 249). Single (n = 145) or tandem (n = 104) auto was optional. Conditioning for the auto arm was melphalan 200 mg/m2; conditioning for the allo arm was total-body irradiation 2 Gy plus fludarabine 30 mg/m2/d for 3 days. Median follow-up time was 61 months. Primary end point was progression-free survival. - - Results - - Progression-free survival at 60 months was significantly better with auto-allo than with allo alone (35% v 18%; P = .001), as was the risk of death and of relapse in the long term (P = .047 and P = .003, respectively). Overall survival at 60 months was 65% versus 58%, and relapse incidence was 49% versus 78%. Complete remission rates were 51% and 41%, respectively (P = .020). Nonrelapse mortality at 24 months was 12% after auto-allo compared with 3% in the auto group (P < .001). The incidence of grade 2 to 4 acute graft-versus-host disease (GvHD) was 20%, and the incidence of limited and extensive chronic GvHD was 31% and 23%. - - Conclusion - - In patients with previously untreated multiple myeloma, long-term outcome with respect to progression-free survival, overall survival, and relapse rate is superior after auto-allo compared with auto only. Nonrelapse mortality is at a reasonable level in both groups.